Subungual Squamous Cell Carcinoma: The Diagnostic Challenge and Clinical Pearls - Wai Leong Kok; Joyce Siong See Lee; Martin Tze-wei Chio (Karger Publishers, 2016)
Subungual squamous cell carcinoma is a rare entity and difficult to diagnose as its clinical presentation may resemble benign conditions. This case report highlights the need to maintain a high clinical index of suspicion, and recommends a practical approach for subungual conditions. Dermoscopy and a biopsy for histology are important adjuncts to clinch the diagnosis.